Mongolia’s Diplomatic Efforts to Join the United Nations and the Changes in the Position of the Great Powers - Denzenlkham, Ulambayar (Mongolian Journal of International Affairs, 2021)
This article discusses Mongolia’s 15 years of diplomatic efforts to join the United Nations, the main factors that influenced it, and the changing policies and positions of the Soviet Union, the Kuomintang of China, the United States, and other great powers. Although the Mongolian People’s Republic was able to join the United Nations in 1946, it was influenced by the Soviet Union’s communist position. Since 1946, Chiang Kai-shek’s Chinese policy and position have been a major obstacle. The history of the Republic of China, which existed on the mainland between 1912 and 1949, was the history of the struggle for power between the warlords, the history of the struggle between the Kuomintang and the Communists. In the nearly 40 years since the founding of the Republic of China in 1912, neither the warlords nor the Kuomintang have been able to exercise their sovereignty on the mainland, but they are keen to see Outer Mongolia as part of their territory. The Kuomintang was expelled from the mainland in 1949, shortly after 1946. During the Korean War, initiated by Kim Il-sung, Joseph Stalin and Mao Zedong, Mongolia stood firmly behind North Korea, providing both moral and material support. It has not been mentioned anywhere that this resulted in Mongolia’s efforts at the UN being postponed for many years. When Communist China entered the Korean War, the Kuomintang, which fully supported the US-led UN military operation (peacekeeping), not only continuously provoked at the Security Council of the United Nations, but also presented false documents about the MPR - described as “a Chinese territory seized by the Soviet Union” - sending troops to North Korea. The United States, which has recognized the status quo of the Mongolian People’s Republic, has made it clear that it has played an important role in the country’s admission to the United Nations. Thus Mongolia’s attempt finally succeeded and it became the 101st state to join the United Nations. As a consequence, Mongolia’s independence has been approved by a recognize of Western powers and it began to emerge out of its isolation, participate in decision of global issues, and cooperate with the international community. However, not only did this opportunity not be fully exploited, but due to the Cold War, Mongolia became a hotbed of ideological competition between the socialist and capitalist systems at the United Nations, the speakers’ rostrum Nevetheless,Post-Cold War, a whole new era of cooperation between Mongolia and the United Nations began.